DEVELOPMENT OF A MODEL FOR IN VITRO CULTURE OF Vallisneria americana Michx. - Ruiz-Carrera, V; Sánchez, AJ (Ecosistemas y Recursos Agropecuarios, 2014)
An exploratory experimental design was developed to establish a model for Vallisneria americana Michx. following conventional in vitro culture procedures for aquatic vegetation. The design included five experiments with stages of presterilization or washing with 0.1% Tween 20R, sterilization with NaClO and poststerilization of explants (leaf base, rhizome, caulinar apex and seeds), and culture in monophasic or biphasic nutrient media. Leaves and rhizo-mes were sterilized with 0.3 and 0.6% NaClO, and contact times of 2.5 and 5 min. Both explants cultured in gellified monophasic White medium with 58.4 mM sacarose and a pH of 7.5 presented on average a 60% contamination by translucid lipidic exudates, followed by darkening. The presterilization of leaves and rhizomes caused the production of exudates, and the addition of 0.01% ascorbic acid to the nutrient medium caused its inhibition. Comparing the White medium with the 0.5 MS medium, both with 0.88 x 10-3mM of bencyladenine, asepsia of explants was impro-ved in White and leaf pigmentation was significantly favored in 0.5 MS, although no explant presented regeneration. Presterilization was omitted in the experiments with caulinar apices and seeds, and sterilization was carried out with 0.6% NaClO for 15 min. The monophasic culture of caulinar apices in liquid 0.5 MS with doses from 0.0 to 8.88 x 10-33 mM of bencyladenine regenerated leaves but resulted in excessive contamination and death.